Studying the effect of storage conditions on the metabolite content of red wine using HILIC LC–MS based metabolomics. (15th April 2016) - Arapitsas, Panagiotis; Corte, Anna Della; Gika, Helen; Narduzzi, Luca; Mattivi, Fulvio; Theodoridis, Georgios
Highlights: Adaptation of a targeted HILIC–MS method to untargeted metabolomics. HILIC–MS untargeted method validation for wine metabolomics. Slightly sub-optimum storage conditions had a major impact in wine metabolome. 4-Amino-heptanedioic acid was annotated for the first time in wine. 4-Amino-heptanedioic acid was a marker for wine sub-optimum storage conditions. Abstract: The main aim of this work was to develop an untargeted normal phase LC–MS method, starting from a targeted method already validated for the analysis of 135 polar metabolites. Since the LC instrument and column were the same, most of the chromatographic conditions remained identical, while the adaptations focused on maintaining the ionic strength of the eluents constant. The sample preparation was simplified and the effectiveness of LC–MS for long batches was evaluated, in order to record the maximum number of metabolites with good chromatographic resolution and the best MS stability and accuracy. The method was applied to study the influence of storage conditions on wine composition. Slightly sub-optimum storage conditions had a major impact on the polar metabolite fingerprint of the red wines analysed and the markers revealed included phenolics, vitamins and metabolites indentified in wine for the first time (4-amino-heptanedioic acid and its ethyl ester).